The value of human life : a study of the story of the flood (Genesis 6-9) - Harland, P. J. (Supplements to Vetus Testamentum,, 1996)
This book examines the way in which the story of the flood in Genesis 6-9 presents the ethical question of the value of human life. The sources J and P are examined to see how their combination in the canonical text enhances interpretation. Several themes of the story are studied including the causes of the flood, the righteousness of Noah, God's repentance, creation and uncreation, the covenant and the image of God. The work concludes by arguing that the value of human life is found in man's relation to God (Gen. 9:6).